Communication practices that encourage and constrain shared decision making in health-care encounters: systematic review of conversation analytic research - Land, Victoria; Parry, Ruth H.; Jane, Seymour (Wiley, 2017)
Background: Shared decision making (SDM) is generally treated as good practice in health-care interactions. Conversation analytic research has yielded detailed findings about decision making in health-care encounters. Objective: To map decision making communication practices relevant to health-care outcomes in face-to-face interactions yielded by prior conversation analyses, and to examine their function in relation to SDM. Search strategy: We searched nine electronic databases (last search November 2016) and our own and other academics’ collections. Inclusion criteria: Published conversation analyses (no restriction on publication dates) using recordings of health-care encounters in English where the patient (and/or companion)was present and where the data and analysis focused on health/illness-related decision making. Data extraction and synthesis: We extracted study characteristics, aims, findings relating to communication practices, how these functioned in relation to SDM, and internal/external validity issues. We synthesised findings aggregatively. Results: Twenty-eight publications met the inclusion criteria. We sorted findings into 13 types of communication practices and organized these in relation to four elements of decision-making sequences: (i) broaching decision making; (ii) putting forward a course of action; (iii) committing or not (to the action put forward); and (iv) HCPs’ responses to patients’ resistance or withholding of commitment. Patients have limited opportunities to influence decision making. HCPs’ practices may constrain or encourage this participation. Conclusions: Patients, companions and HCPs together treat and undertake decision making as shared, though to varying degrees. Even for non-negotiable treatment trajectories, the spirit of SDM can be invoked through practices that encourage participation (eg by bringing the patient towards shared understanding of the decision’s rationale).